Identification of Foot Complaints in Patients with DM, Descriptive Study - Joeliantina, Anita (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2025)
Diabetic foot ulcers (DFUs) are a common complication of diabetes mellitus (DM) and cause significant morbidity and mortality. Diabetic feet exhibit various structural and functional changes compared to non-diabetic feet. The purpose of this study was to identify foot complaints commonly experienced by patients with DM. This study employed a descriptive design with a cross-sectional approach. The sample size was 200 adult patients with DM selected using a purposive sampling technique. Patients with DM were asked to provide written consent before completing the questionnaire. This study used descriptive analysis, using a frequency distribution table. Data on foot complaints of patients with DM showed that numbness or thickening of the feet was present in 28.5%, tingling in 32.5%, and numbness in the feet was less common, with only 7.0% reporting consistent experience. Meanwhile, 13.0% experienced itchy feet, and only 3.0% reported persistent reddish feet. Blackish feet, a more serious condition, were recorded with 12.5% reporting persistent blackness. Swelling in the feet was reported by 6.0% and pain in the feet was reported by 15.0%. All patients with diabetes in the study experienced complaints in their feet, some even having more than one foot complaint. Among these foot complaints, numbness/thickness, tingling, and pain are common among patients with diabetes. Patients with DM should receive accurate information to identify foot complaints of developing Diabetic foot ulcer and to prevent them by performing proper and regular foot care